KADAR HARA NPK TANAMAN KELAPA SAWIT PADA BERBAGAI TINGKAT KEMATANGAN TANAH GAMBUT DI PERKEBUNAN KELAPA SAWIT PT. PENITI SUNGAI PURUN KABUPATEN MEMPAWAH - Bayu Saputra; Denah Suswati; Rini Hazriani (Perkebunan dan Lahan Tropika, 2021)
Nutrient levels is the process to determine the present nutrient content in tissue plant. Nutrient levels obtained through field survey and nutrient analysis in the laboratory. This research aims to determine levels of N, P and K as well as recommend the use of N, P, and K for oil palm plants so as to increase the production of palm oil. This research was conducted at PT. Peniti Sungai Purun, MempawahRegency. The analysis results showed that the levels of N, P, and K on all blocks belonging to deficiency until optimum. In each block, the dose recommend of fertilizer N, P, and K to block G50 (1,73 kg urea/tree/year, 1,50 kg Rock Phospate/tree/4 times/year, and 2,50 kg KCl/tree/year) Blocks H34 (3,00 kg urea/tree/year, 3,50 kg Rock Phospate/tree/year, and 3,50 kg KCl/tree/year). Block I26 (1,73 kg urea/tree/year, 1,50 kg Rock Phospate/tree/year, and 2,50 kg KCl/tree/year). Block J26 (3,00 kg urea/tree/year, 3,50 kg Rock Phospate/tree/ year, and 3,50 kg KCl/tree/year). This dosage recommendations are used to increase the production of oil palm plants in PT. Peniti Sungai Purun.Keywords : Nutrient levels, recommendation of fertilization .